答:
tan(x+π/4)=3
[ tanx+tan(π/4) ] / [1-tanx*tan(π/4) ]=3
(1+tanx) /(1-tanx)=3
1+tanx=3-3tanx
4tanx=-2
tanx=sinx/cosx=-1/2
sinx=(-1/2)cosx
代入(sinx)^2+(cosx)^2=1得:
(1/4)*(cosx)^2+(cosx)^2=1
解得:(cosx)^2=4/5
所以:tanx=sinx/cosx=sinxcosx/(cosx)^2=-1/2
所以:sinxcosx=-(1/2)*(cosx)^2=-(1/2)*(4/5)=-2/5
所以:sinxcosx=-2/5懂了谢谢7顺便说哈tanx是二分之一你加错了对不起,失误了:
答:
tan(x+π/4)=3
[ tanx+tan(π/4) ] / [1-tanx*tan(π/4) ]=3
(1+tanx) /(1-tanx)=3
1+tanx=3-3tanx
4tanx=2
tanx=sinx/cosx=1/2
sinx=(1/2)cosx
代入(sinx)^2+(cosx)^2=1得:
(1/4)*(cosx)^2+(cosx)^2=1
解得:(cosx)^2=4/5
所以:tanx=sinx/cosx=sinxcosx/(cosx)^2=1/2
所以:sinxcosx=(1/2)*(cosx)^2=(1/2)*(4/5)=2/5
所以:sinxcosx=2/5